Effect of eplerenone on aldosterone and von Willebrand factor levelsin patients with myocardial infarction and chronic kidney disease - Tashchuk, V. K.; Polianska, O. S.; Hulaha, O. I. (Zaporozhye Medical Journal, 2022)
Aim: to study the levels of aldosterone and von Willebrand factor (VWF) in patients with Q-wave acute myocardial infarction (Q-AMI) and underling chronic kidney disease (CKD) using aldosterone antagonists. Materials and methods. The study group consisted of 106 patients with renal dysfunction who were hospitalized for acute Q-AMI. Serum levels of neurohumoral parameters (aldosterone and VWF) were determined in all the patients by enzyme-linked immunosorbent assay kits. Results. Reduction in the aldosterone levels was found in patients with Q-AMI and stage 2 CKD from 245.08 ± 17.38 pmol/l to 195.15 ± 13.82 pmol/l (P < 0.05;) who received spironolactone and from 275.59 ± 23.43 to 169.37 ± 24.46 pmol/l (P < 0.001) with eplerenone usage. Patients with stage 1 CKD showed a decreasing trend in aldosterone levels when using spironolactone (from 238.04 ± 20.37 pmol/l to 200.78 ± 9.15 pmol/l), and significantly decreased aldosterone levels when receiving eplerenone (from 229.77 ± 13.76 pmol/l to 156.76 ± 5.76 pmol/l; P < 0.05). The serum concentration of VWF in stage 2 CKD patients was changed insignificantly on spironolactone therapy (from 0.99 ± 0.13 mg/l to 1.13 ± 0.06 mg/l) and it was significantly decreased in the eplerenone group – from 1.29 ± 0.19 mg/l to 0.71 ± 0.14 mg/l (P < 0.05). In stage 1 CKD patients, the concentration of VWF was not decreased significantly with the use of spironolactone (from 1.22 ± 0.13 mg/l to 1.03 ± 0.06 mg/l), but it was decreased significantly when receiving eplerenone (from 1.14 ± 0.09 mg/l to 0.79 ± 0.08 mg/l; P < 0.05). The data obtained indicate the significantly higher probability of declining both aldosterone (t = 2.91; P < 0.01) and VWF (t = 2.59; P < 0.01) with the use of eplerenone in the complex treatment as compared to the spironolactone administration. Conclusions. The effect of eplerenone to decrease the concentration of aldosterone and VWF is significantly greater than that of spironolactone, especially in AMI patients with stage 2 CKD.